Helical repeat of DNA in the region of homologous pairing - Kiianitsa, Konstantin (The National Academy of Sciences of the USA, 1997)
The process of DNA strand exchange during general genetic recombination is initiated within protein-stabilized synaptic filaments containing homologous regions of interacting DNA molecules. The RecA protein in bacteria and its analogs in eukaryotic organisms start this process by forming helical filamentous complexes on single-stranded or partially single-stranded DNA molecules. These complexes then progressively bind homologous double-stranded DNA molecules so that homologous regions of single- and double-stranded DNA molecules become aligned in register while presumably winding around common axis. The topological assay presented herein allows us to conclude that in synaptic complexes containing homologous single- and double-stranded DNA molecules, all three DNA strands have a helicity of approximately 19 nt per turn.